NGRINGKÃS Adaptasi Garap Pertunjukan Hiburan JÃªmblungan Desa Samiran Kecamatan Selo Kabupaten Boyolali - , Galih Suryadmaja ([Yogyakarta] : Universitas Gadjah Mada, 2014)
In the change, the performing arts have a different concept. It is one of had happened on Jêmblungan. Previously it's used as a medium for the spread of religion (da'wah), in its development has been used as a medium of entertainment. Within this change, Jêmblungan also adjust (adapt) from the changes that occur with implement ngringkês to change garap of the performing arts. In this study, to understand the Jêmblungan's phenomenon is limited to the issue (a) How ngringkês as a form of adaptation of garap Jêmblungan